How palatal vault morphology and screw length influence the accuracy of dynamic computer-guided orthodontic miniscrew insertion. A prospective clinical study - Brilli, Davide; Cauli, Isabella; Cassetta, Michele (Journal of dentistry, 2024)
•Palatal vault morphology is one of the factors that influence the accuracy of palatal orthodontic miniscrew insertion in dynamic computer-guided surgery.•Miniscrew length does not influence the insertion accuracy in any deviation parameter.•The angular parameter is affected by the shape of the palatal vault, with significant differences observed between high/steep when compared to a normal or wide morphology.•Although dynamic computer-guided surgery assists the clinician in preventing damages to nearby anatomical structures, it is crucial to consider individual anatomical variability. The aim of this study was to evaluate the influence of palatal vault morphology and screw length on the accuracy of miniscrew insertion in dynamic computer-assisted surgery (d-CAS). Twenty-four subjects were allocated into three groups, according to their palatal vault morphology (Group A: medium; Group B: steep/high; Group C: low/flat) and the length of miniscrew used. For each subject, two miniscrews were inserted using a dynamic navigation system. To assess the accuracy of insertion, a postoperative CBCT was performed, and the pre- and post-operative scans were superimposed. Five variables were evaluated: Entry-3D, Entry-2D, Apex-3D, Apex-vertical and angular deviation. Descriptive statistics, Shapiro-wilk, Kruskal-Wallis and Dunn's tests were used for the statistical analysis. The level of significance was P ≤ 0.05. The mean angular deviation values revealed strong discrepancies amongst the groups (Group A:7.11°±5.70°; Group B:13.30°±7.76°; Group C:4.92°±3.15°) and significant differences were found regarding the Apex-3D (P = 0.036) and angular deviations (P = 0.008). A Dunn's test revealed differences in angular deviation between the medium and high/steep palate group (P = 0.004), and between low/flat and high/steep palate group (P = 0.01) but did not confirm any significant difference in the Apex-3D parameter (Group A-B P = 0.10; Group B-C, P = 0.053; Group A-C, P = 1.00). No significant differences were found regarding the length of the miniscrews. Palatal vault morphology is a factor that influences the accuracy of miniscrew insertion in d-CAS. In subjects with steep and high palatal vaults, insertion accuracy is lower when considering the angular deviation value. Miniscrew length does not influence accuracy. Although computer-guided surgery assists the clinician in preventing damage to nearby anatomical structures, individual anatomical variability is a crucial variable. In subjects with a high/steep palate, greater attention should be paid during the planning phase in order to allow for a wide margin from adjacent anatomical structures to achieve better outcomes.